Do children favor snacks and dislike vegetables? Exploring children's food preferences using drawing as a projective technique. A cross-cultural study. (1st October 2021) - Ragelienė, Tija
Abstract: Objective: To avoid the rising spread of childhood obesity and preserve resources within planetary boundaries, healthy and sustainable eating habits and the consumption of adequate amounts of fruits and vegetables should be encouraged. Children's food preference was found to be an important determinant for food choice and consumption. The aim of this study was to explore children's food preferences using drawing as a projective technique in terms of healthy and sustainable eating and compare food preference patterns in Denmark and Lithuania. Method: In total 484 children, aged between 8 and 13 years old, participated in the study (147 in Denmark and 337 in Lithuania). Participants were asked to fill the food preference questionnaire and answer questions about their daily intake of fruits, vegetables, and snacks and draw their favorite meal afterward. Sociodemographic questions about children's age, gender, parents' employment, and family composition were also included in the questionnaire. Results: Fruits, vegetables, highly-processed and animal-based foods were not included in a large part of children's most preferred meal composition. Favorite meals' composition varied among children in both countries and included different products from separate food groups. Vegetables were more likely to be present in the children's favorite meals together with meat products. Girls in both countries had more expressed vegetable preferences than boys. Boys in Lithuania had a relatively more expressed preference for highly-processed foods, while Danish girls had a more expressed preference for animal-based products. Conclusions: Children's preferences for foods such as meat and animal-based products expressed in children's drawings, might be considered as relatively positive in terms of sustainable eating. However, children's preferences and intake of fruits and vegetables should still be encouraged among young consumers. Cultural and gender differences in children's food preferences should be considered while creating interventions and marketing strategies for promoting healthy and sustainable eating among young consumers.